Boron carbide ceramic as well as preparation method and application thereof

By depositing an ultra-thin titanium film on the surface of the boron carbide ceramic blank and forming a multi-layered superposition structure, the tough phase is sintered at high temperature, which solves the problems of brittleness and poor toughness of boron carbide ceramics, and significantly improves its bending strength and elastic resistance.

CN119707495APending Publication Date: 2025-03-28新兴际华(上海)工程科技研究院有限公司
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411913895.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-24
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

Boron carbide ceramics are prone to disintegration and fragmentation when subjected to high-speed invasion and impact, resulting in insufficient bulletproof performance.

Method used

The surface of the molded plate-shaped boron carbide blank is formed by magnetron sputtering, and the composite boron carbide blank is formed by multi-layer ordered overlapping titanium-coated boron carbide blank. When sintered at high temperature, the surfaces of the adjacent blanks react in situ to form tough phases such as titanium boron carbide and titanium carbide, forming a multi-layer parallel array distributed tough array.

Benefits of technology

It improves the bending strength and elastic resistance of boron carbide ceramics, and the distribution continuity of tough arrays is good, uniformity is high, easy to adjust, simple process, and is suitable for industrial mass production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119707495A_ABST
    Figure CN119707495A_ABST
Patent Text Reader

Abstract

The invention discloses boron carbide ceramic as well as a preparation method and application thereof. The preparation method of the boron carbide ceramic comprises the following steps: S1, depositing a pure titanium film on a single surface of a plate-shaped boron carbide biscuit subjected to compression molding to obtain a titanium-coated boron carbide biscuit; s2, the multiple titanium-coated boron carbide biscuits are stacked in order in the thickness direction, and a composite boron carbide biscuit with multiple layers of titanium films distributed at intervals is obtained; wherein the titanium film surfaces and the titanium-free film surfaces of two adjacent titanium-coated boron carbide biscuits are attached to each other; and S3, sintering the composite boron carbide biscuit with the multiple layers of titanium films distributed at intervals, and meanwhile, carrying out an in-situ reaction between two adjacent boron carbide biscuits to generate a tough layer, so as to obtain the boron carbide ceramic. The toughening structure with the toughness layers distributed at intervals is constructed in the boron carbide ceramic matrix, the toughness layers are distributed in the boron carbide ceramic matrix in a multi-layer parallel array mode, the continuity is good, the uniformity is high, and finally the bending strength and the anti-elasticity performance of the boron carbide ceramic are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of boron carbide ceramics, in particular to a boron carbide ceramic and a preparation method and application thereof, which is mainly used for protective products such as individual soldier inserts and bulletproof armor. Background Art

[0002] Boron carbide ceramics have the characteristics of high hardness, light weight, high temperature resistance and corrosion resistance, and are often used in protective products such as individual armor plates and bulletproof armor. However, boron carbide ceramics are inorganic materials with only covalent bonds between molecules, so they are brittle and easily disintegrate and break when hit by high-speed penetration of bullets or fragments. Therefore, improving the bending strength and fracture toughness of boron carbide ceramics is the main way to improve its anti-ballistic performance.

[0003] At present, the method used in the industry to improve the bending strength and fracture toughness of boron carbide ceramics is usually to add a second phase, such as graphene, boron nitride, silicon carbide, titanium boride, etc., to the boron carbide matrix to form a composite ceramic, thereby improving the anti-ballistic performance of boron carbide ceramics. Patents CN108530082A, CN103833403B, CN113004052B, and CN115745642B respectively add graphene, silicon carbide whiskers, multi-walled carbon nanotubes, and chopped fibers to boron carbide to increase crack propagation resistance, change the crack propagation path, and improve the fracture toughness and bending strength of boron carbide ceramics; in the preparation process of the above-mentioned ceramics, the second phase is mostly powder or short fibers, which are dispersed in the boron carbide matrix after being mixed with boron carbide powder and ball-milled, that is, a large number of tough particles are distributed in the boron carbide matrix after sintering into porcelain; the disadvantage is that, due to the grinding and dispersing ability of the ball milling process, when the particle size of the second phase is small, it cannot be fully mixed with the boron carbide powder, and finally there is local agglomeration or enrichment of the second phase at the microscopic level. Patent CN113896552B lays continuous silicon carbide fiber fabric in boron carbide powder to reinforce the boron carbide ceramic matrix, forming a reinforcement array, and at the same time, the titanium source on the fiber surface is transformed into a tough phase at high temperature, further forming a tough array, so it has a good reinforcement and toughening effect; but the disadvantage is that if the silicon carbide fiber fabric used is relatively dense and the fiber is twisted during weaving, it is difficult for the boron carbide powder to fully penetrate between the fiber filaments when pressing the boron carbide ceramic blank; if the silicon carbide fiber fabric used is relatively sparse and the structure of the fabric itself is loose, then when the ceramic blank is pressed after being coated with boron carbide powder, during the process of powder compaction under high pressure, the fibers in the fabric are displaced, resulting in the destruction of structural consistency and integrity; therefore, although this patent effectively improves the bending strength and fracture toughness of the ceramic, it is difficult to avoid potential structural defects in the molding process, resulting in increased discreteness of ceramic properties. Patent CN115741976A uses a three-dimensional metal fabric with a 3D structure to toughen and strengthen the boron carbide ceramic matrix. However, when the ceramic body is squeezed in a mold, the 3D fabric is prone to structural collapse and it is difficult to maintain its integrity. Summary of the invention

[0004] In view of the existing problems of brittleness, poor toughness and low bending strength of boron carbide ceramics for bulletproof products, the present invention aims to provide a boron carbide ceramic and a preparation method and application thereof. The boron carbide ceramic forms an ultra-thin pure titanium film on the surface of a plate-shaped boron carbide ceramic blank formed by compression molding by magnetron sputtering, and then when a composite boron carbide blank composed of multiple layers of orderly stacked titanium-coated boron carbide thin plate-shaped blanks is sintered at a high temperature, adjacent blank surfaces react in situ to form tough phases such as titanium boride and titanium carbide, and the tough phases are distributed in a multi-layer parallel array in the boron carbide ceramic matrix, with good continuity and high uniformity, and finally the bending strength and anti-ballistic performance of the boron carbide ceramic are improved.

[0005] To achieve the above object, the present invention adopts the following technical solution:

[0006] In a first aspect, the present invention provides a method for preparing a boron carbide ceramic, comprising the following steps:

[0007] S1, depositing a pure titanium film on one side of a plate-shaped boron carbide blank formed by compression molding to obtain a titanium-clad boron carbide blank;

[0008] S2. Stacking a plurality of the titanium-coated boron carbide blanks in an orderly manner along the thickness direction to obtain a composite boron carbide blank with multiple layers of titanium films spaced apart; wherein the orderly stacking is to laminate the titanium film surface and the titanium-free film surface of two adjacent titanium-coated boron carbide blanks;

[0009] S3, sintering the composite boron carbide blank with the multi-layer titanium film spaced apart, and simultaneously generating a toughness layer by in-situ reaction between two adjacent boron carbide blanks to obtain the boron carbide ceramic.

[0010] Based on the above technical scheme, the present invention takes a different approach and generates an ultra-thin pure titanium film on the surface of a compression-molded plate-shaped boron carbide blank by magnetron sputtering. Then, when a composite boron carbide blank composed of a plurality of stacked titanium-coated boron carbide thin plate-shaped blanks is sintered at a high temperature, the surfaces of adjacent blanks react in situ to generate tough phases such as titanium boride and titanium carbide, and the tough phases are distributed in a multi-layer parallel array in the boron carbide ceramic matrix, thereby ultimately improving the bending strength and anti-elastic performance of the boron carbide ceramic.

[0011] In the above method for preparing boron carbide ceramics, in step S1, the thickness of the titanium film is 0.10 μm to 5.00 μm, preferably 0.10 μm to 1.00 μm.

[0012] In the above method for preparing boron carbide ceramics, in step S1, the thickness of the plate-shaped boron carbide blank is 2 mm to 5 mm.

[0013] In the above-mentioned method for preparing boron carbide ceramics, in step S1, the deposition process of the titanium film includes any one of magnetron sputtering, physical vapor deposition, chemical vapor deposition, vacuum evaporation, ion implantation, plasma spraying, and chemical plating, such as magnetron sputtering.

[0014] Furthermore, the conditions of the magnetron sputtering are as follows: the magnetron sputtering is DC magnetron sputtering, and the operation is as follows: vacuum is evacuated to 1.5×10 -4 Pa, fill with 99.99% pure argon to 0.5Pa and maintain the argon flow rate at 30ml / min~50ml / min, maintain the sputtering power at 250W and the cathode negative bias at 80V, use a 99.9% pure titanium target, and deposit for 2min~60min.

[0015] In the above-mentioned method for preparing boron carbide ceramics, in step S1, the method for preparing the plate-like boron carbide blank comprises the following steps: S11, mixing boron carbide powder, a binder and a solvent by ball milling, spray granulating and drying in sequence to obtain boron carbide granules; S12, pouring the boron carbide granules into a mold cavity for compression molding to obtain the plate-like boron carbide blank.

[0016] Further, the boron carbide powder includes boron carbide powder with a D90 of 1 μm to 4 μm and boron carbide powder with a D90 of 0.05 μm to 0.80 μm in a mass ratio of (3 to 7): 1;

[0017] The binder is phenolic resin or polyvinyl alcohol;

[0018] The mass of the binder is 1% to 8% of the boron carbide powder;

[0019] The solvent is ethanol or water;

[0020] The mass ratio of the boron carbide powder to the solvent is 1:(3-7);

[0021] The ball milling time is 20min to 40min;

[0022] The drying temperature is 40°C to 110°C;

[0023] The mesh number of the boron carbide pellets is 80 mesh to 120 mesh;

[0024] The compression molding process includes a first compression and a second compression. The first compression is performed at room temperature and 100 MPa for 2 minutes, and the second compression is performed at room temperature and 150 MPa for 1 minute.

[0025] In the above-mentioned method for preparing boron carbide ceramics, in step S2, the upper and lower outer surfaces of the composite boron carbide blank are free of titanium film;

[0026] In step S2, the total thickness of the composite boron carbide blank with the multi-layer titanium film spaced apart is 8 mm to 15 mm;

[0027] In step S3, the sintering includes local reaction sintering and overall hot pressing sintering performed successively; the pressure of the local reaction sintering is 15MPa~30MPa, the temperature is 1600℃~1700℃, and the insulation and pressure holding time is 10min~30min; the pressure of the overall hot pressing sintering is 30MPa~40MPa, the temperature is 2000℃~2300℃, and the insulation and pressure holding time is 60min~120min.

[0028] In a second aspect, the present invention provides a boron carbide ceramic prepared by any of the above-mentioned methods for preparing the boron carbide ceramic.

[0029] In a third aspect, the present invention provides the use of the boron carbide ceramic in individual soldier plates or bulletproof armor.

[0030] The present invention has the following beneficial effects:

[0031] Compared with the existing technologies and products, the present invention has the following advantages: ① the tough phase in the boron carbide matrix is ​​distributed in a multi-layer parallel array with good continuity and high uniformity; ② the thickness, spacing, density and quantity of the tough array are flexibly adjustable, and it is easy to design and produce according to local conditions based on equipment capacity and product needs; ③ the preparation process is simple, with good repeatability, and it is easy to industrialize and mass produce. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 The schematic diagram of the method for preparing the boron carbide ceramic of the present invention is to stack a plurality of titanium-coated boron carbide blanks in an orderly manner. The symbols in the figure are as follows: 1-boron carbide blank; 2-titanium film. DETAILED DESCRIPTION

[0033] In order to make the purpose, technical solution and advantages of the embodiment of the present invention clearer, the technical solution of the embodiment of the present invention will be clearly and completely described below in conjunction with the drawings of the embodiment of the present invention. Obviously, the described embodiment is a part of the embodiment of the present invention, not all of the embodiments. Based on the described embodiment of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0034] In the description of the present invention, it should be noted that the terms "upper" and "lower" etc. indicate directions or positional relationships based on the directions or positional relationships shown in the accompanying drawings, and are only for the convenience of describing the present invention and simplifying the description, rather than indicating or implying that the system or element referred to must have a specific direction, be constructed and operated in a specific direction, and therefore cannot be understood as a limitation on the present invention.

[0035] like Figure 1As shown, in the first part, a method for preparing a boron carbide ceramic provided by the present invention comprises the following steps: S1, depositing a pure titanium film 2 on a single surface of a molded plate-shaped boron carbide blank 1 to obtain a titanium-coated boron carbide blank; S2, stacking a plurality of the titanium-coated boron carbide blanks in an orderly manner along the thickness direction to obtain a composite boron carbide blank with a multi-layer titanium film spaced apart; wherein the orderly stacking is the lamination of the titanium film surface and the titanium-free film surface of two adjacent titanium-coated boron carbide blanks; S3, sintering the composite boron carbide blank with a multi-layer titanium film spaced apart, and at the same time, reacting in situ between the two adjacent boron carbide blanks to generate a toughness layer to obtain the boron carbide ceramic. In the boron carbide ceramic prepared by the method of the present invention, the adjacent blank surfaces react in situ to generate tough phases such as titanium boride and titanium carbide, and the tough phases are distributed in a multi-layer parallel array in the boron carbide ceramic matrix, which ultimately improves the bending strength and anti-elastic performance of the boron carbide ceramic.

[0036] In some embodiments of the present invention, in step S1, the thickness of the titanium film is 0.10 μm to 5.00 μm, such as 0.3 μm to 2.4 μm, preferably 0.10 μm to 1.00 μm, including but not limited to 0.3 μm to 0.6 μm, 0.3 μm or 0.6 μm. The thickness of the titanium film can be adjusted within a reasonable range according to the product requirements of the boron carbide ceramic. When the thickness is too thin, the expected bending strength and anti-elastic performance cannot be obtained due to the limited toughness phase generated by the in-situ reaction, and when the thickness is too thick, it will cause local deformation of the product.

[0037] In some embodiments of the present invention, in step S1, the thickness of the plate-shaped boron carbide blank is 2 mm to 5 mm, such as 2 mm to 3 mm. The thickness of the plate-shaped boron carbide blank, the thickness of the composite boron carbide blank, and the amount of the toughness layer need to be flexibly designed based on the thickness, bending strength, and anti-elastic performance requirements of the sintered boron carbide ceramic during actual use, and can be adjusted within a reasonable range according to product needs.

[0038] In some embodiments of the present invention, optionally, in step S1, the titanium film deposition process includes any one of magnetron sputtering, physical vapor deposition, chemical vapor deposition, vacuum evaporation, ion implantation, plasma spraying, and chemical plating, but is by no means limited thereto. As long as the process can completely deposit the titanium film on the surface of the plate-like boron carbide blank, it is within the protection scope of the present invention. Preferably, the conditions of the magnetron sputtering are as follows: the magnetron sputtering is DC magnetron sputtering, and the operation is as follows: evacuate to 1.5×10 -4Pa, fill with 99.99% pure argon to 0.5Pa and keep the argon flow rate at 30ml / min~50ml / min (such as 30ml / min or 40ml / min), keep the sputtering power at 250W and the cathode negative bias at 80V, use a 99.9% pure titanium target, and deposit for 2min~60min. The purity of the titanium film obtained under this operating condition can reach 99.5%~99.8%, and the high-purity titanium film can better react with the adjacent green billet surface to generate a tough phase through in-situ sintering. The deposition time can be reasonably selected according to the thickness of the titanium film.

[0039] In some embodiments of the present invention, in step S1, the method for preparing the plate-like boron carbide blank comprises the following steps: S11, mixing boron carbide powder, a binder and a solvent by ball milling, spray granulating and drying in sequence to obtain boron carbide granules; S12, pouring the boron carbide granules into a mold cavity for compression molding to obtain the plate-like boron carbide blank. Optionally, the boron carbide powder comprises a boron carbide powder with a D90 of 1 μm to 4 μm and a boron carbide powder with a D90 of 0.05 μm to 0.80 μm in a mass ratio of (3 to 7): 1, such as a boron carbide powder with a D90 of 3 μm and a boron carbide powder with a D90 of 0.5 μm in a mass ratio of 5:1 or 4:1; the binder is phenolic resin or polyvinyl alcohol; the mass of the binder is 1% to 8% of the boron carbide powder, such as 1.5%, 3% or 5%; the solvent is ethanol or water; the mass ratio of the boron carbide powder to the solvent is 1:(3 to 7), such as 1:5; the mass ratio of the boron carbide powder to the solvent is Controlling within this range is conducive to improving the ball milling efficiency, so that the boron carbide powder, binder and solvent are fully mixed and uniform; the ball milling time is 20min to 40min, such as 30min; the drying temperature is 40℃ to 110℃, such as 50℃ or 110℃; the mesh size of the boron carbide granules is 80 mesh to 120 mesh; the pressing process includes a first pressing and a second pressing; the first pressing is to maintain the pressure at room temperature and 100MPa for 2min, and the second pressing is to maintain the pressure at room temperature and 150MPa for 1min; wherein, room temperature refers to 10℃ to 30℃, preferably 20℃ to 25℃, such as 25℃.

[0040] In some embodiments of the present invention, in step S2, a plurality of the titanium-coated boron carbide blanks are orderly stacked along the thickness direction to obtain a composite boron carbide blank with multiple layers of titanium films spaced apart; wherein the orderly stacking is that the titanium film surface and the non-titanium film surface of two adjacent titanium-coated boron carbide blanks are bonded together, and the upper and lower outer surfaces of the composite boron carbide blank with multiple layers of titanium films spaced apart are free of titanium film; those skilled in the art may choose to use a plate-like boron carbide blank without a pure titanium film deposited on it for stacking at the top or bottom layer as needed.

[0041] In some embodiments of the present invention, in step S2, the total thickness of the composite boron carbide blank with multiple layers of titanium films spaced apart is 8 to 15 mm, such as 10 mm, 11 mm, 12 mm, 13 mm or 14 mm, and those skilled in the art can make a reasonable selection within this range according to product performance requirements.

[0042] In some embodiments of the present invention, in step S3, the sintering includes local reaction sintering and overall hot pressing sintering performed successively; the pressure of the local reaction sintering is 15MPa~30MPa (such as 20MPa), the temperature is 1600℃~1700℃ (such as 1650℃), and the insulation and pressure holding time is 10min~30min (such as 20min or 25min); the pressure of the overall hot pressing sintering is 30MPa~40MPa (such as 35MPa), the temperature is 2000℃~2300℃ (such as 2050℃), and the insulation and pressure holding time is 60min~120min (such as 90min).

[0043] In the second part, the present invention provides a boron carbide ceramic prepared by the preparation method of the boron carbide ceramic described in any one of the above items.

[0044] In the third part, the present invention provides the application of the boron carbide ceramic in individual soldier plates or bulletproof armor.

[0045] The present invention is further described in detail below in conjunction with specific embodiments, and the examples provided are only for illustrating the present invention, rather than for limiting the scope of the present invention. The examples provided below can be used as a guide for further improvements by those of ordinary skill in the art, and do not constitute a limitation of the present invention in any way.

[0046] The methods used in the following examples, unless otherwise specified, are all conventional methods, carried out according to the techniques or conditions described in the literature in the art or according to the product instructions. The materials, reagents, etc. used in the following examples, unless otherwise specified, can all be obtained from commercial sources.

[0047] Example 1: Preparation of Boron Carbide Ceramics

[0048] The specific steps are as follows:

[0049] First, a commercially available phenolic resin (model: PF9502, Jinan Shengquan Group Co., Ltd.) was dissolved in anhydrous ethanol to form a solution with a concentration of 1 wt%.

[0050] Then, commercially available boron carbide powder with a D90 of 3 μm and boron carbide powder with a D90 of 0.5 μm (supplier: Mudanjiang Diamond Boron Carbide Co., Ltd.) were weighed at a mass ratio of 5:1, preliminarily mixed evenly, put into a grinding jar, and then further added with a prepared "phenolic resin + anhydrous ethanol" mixed solution (after conversion, the mass ratio of phenolic resin: boron carbide powder: anhydrous ethanol was 5:100:500), mixed and dispersed in a ball mill for 30 minutes, spray granulated and dried at 50°C to form boron carbide granules.

[0051] Subsequently, an appropriate amount of 80-120 mesh boron carbide granules was sieved and weighed, poured into the mold cavity, and maintained at 100 MPa for 2 minutes and 150 MPa for 1 minute at room temperature to form a boron carbide thin plate blank with a thickness of 2 mm to 3 mm, which was then dried at room temperature.

[0052] Afterwards, the boron carbide sheet blank was transferred to the chamber of the DC magnetron sputtering equipment and evacuated to 1.5×10 - 4 Pa, fill with 99.99% pure argon to 0.5Pa and maintain the argon flow rate at 30ml / min, maintain the sputtering power at 250W and the cathode negative bias at 80V, use a 99.9% pure titanium target, deposit for 15min, and form an ultra-thin pure titanium film with a thickness of about 0.30μm on the surface of the boron carbide thin plate-like blank.

[0053] Finally, the boron carbide thin plate blank with a single-sided sputtering coating of pure titanium film is stacked in multiple layers to a cumulative thickness of 13 mm, with the upper and lower surfaces exposed to the outside kept free of titanium film. The whole is wrapped with graphite paper and transferred to a graphite mold, and local reaction sintering and overall hot pressing sintering are carried out in sequence. The pressure of the local reaction sintering is 20 MPa, the temperature is 1650°C, and the insulation time is 20 min; the pressure of the overall hot pressing sintering is 35 MPa, the temperature is 2050°C, and the insulation time is 90 min, so that the boron carbide powder is completely porcelainized and taken out of the furnace after cooling.

[0054] Example 2: Preparation of Boron Carbide Ceramics

[0055] The specific steps are as follows:

[0056] First, commercially available polyvinyl alcohol (model: 088-20, China Petrochemical Group Chongqing Chuanwei Chemical Co., Ltd.) was dissolved in deionized water to form a solution with a concentration of 1 wt%.

[0057] Then, commercially available boron carbide powder with a D90 of 3 μm and boron carbide powder with a D90 of 0.5 μm (supplier: Mudanjiang Diamond Boron Carbide Co., Ltd.) were weighed at a mass ratio of 4:1 and preliminarily mixed evenly, put into a grinding tank, and then further added with a prepared polyvinyl alcohol aqueous solution (after conversion, the mass ratio of polyvinyl alcohol: boron carbide powder: deionized water was 5:100:500), mixed and dispersed in a ball mill for 30 minutes, spray granulated and dried at 110°C to form boron carbide granules.

[0058] Subsequently, an appropriate amount of 80-120 mesh boron carbide granules was sieved and weighed, poured into the mold cavity, and maintained at 100 MPa for 2 minutes and 150 MPa for 1 minute at room temperature to form a boron carbide thin plate blank with a thickness of 2 mm to 3 mm, which was then dried at room temperature.

[0059] Afterwards, the boron carbide sheet blank was transferred to the chamber of the DC magnetron sputtering equipment and evacuated to 1.5×10 - 4 Pa, fill with 99.99% pure argon to 0.5Pa and maintain the argon flow rate at 40ml / min, maintain the sputtering power at 250W and the cathode negative bias at 80V, use a 99.9% pure titanium target, and deposit at room temperature for 30min to form an ultra-thin pure titanium film with a thickness of about 0.60μm on the surface of the boron carbide thin plate-like blank.

[0060] Finally, the boron carbide thin plate blank with a single-sided sputtering coating of pure titanium film was stacked in multiple layers to a cumulative thickness of 14 mm, with the upper and lower surfaces exposed to the outside kept free of titanium film. The whole was wrapped with graphite paper and transferred to a graphite mold, and local reaction sintering and overall hot pressing sintering were carried out in sequence. The pressure of the local reaction sintering was 20 MPa, the temperature was 1650°C, and the insulation time was 25 min; the pressure of the overall hot pressing sintering was 35 MPa, the temperature was 2050°C, and the insulation time was 90 min, so that the boron carbide powder was completely porcelainized and then taken out of the furnace after cooling.

[0061] Example 3: Preparation of Boron Carbide Ceramics

[0062] The specific steps are as follows:

[0063] First, commercially available polyvinyl alcohol (model: 088-20, China Petrochemical Group Chongqing Chuanwei Chemical Co., Ltd.) was dissolved in deionized water to form a solution with a concentration of 1 wt%.

[0064] Then, commercially available boron carbide powder with a D90 of 3 μm and boron carbide powder with a D90 of 0.5 μm (supplier: Mudanjiang Diamond Boron Carbide Co., Ltd.) were weighed at a mass ratio of 4:1 and preliminarily mixed evenly, put into a grinding tank, and then further added with a prepared polyvinyl alcohol aqueous solution (after conversion, the mass ratio of polyvinyl alcohol: boron carbide powder: deionized water was 5:100:500), mixed and dispersed in a ball mill for 30 minutes, spray granulated and dried at 110°C to form boron carbide granules.

[0065] Subsequently, an appropriate amount of 80-120 mesh boron carbide granules was sieved and weighed, poured into the mold cavity, and subjected to 100 MPa pressure holding for 2 min and 150 MPa pressure holding for 1 min at room temperature to form a boron carbide thin plate blank with a thickness of 2 mm to 3 mm, which was then dried at room temperature.

[0066] Afterwards, the boron carbide sheet blank was transferred to the chamber of the DC magnetron sputtering equipment and evacuated to 1.5×10 - 4 Pa, fill with 99.99% pure argon to 0.5Pa and maintain the argon flow rate at 40ml / min, maintain the sputtering power at 250W and the cathode negative bias at 80V, use a 99.9% pure titanium target, and deposit at room temperature for 120min to form an ultra-thin pure titanium film with a thickness of about 2.4μm on the surface of the boron carbide thin plate-like blank.

[0067] Finally, the boron carbide thin plate blank with a single-sided sputtering coating of pure titanium film was stacked in multiple layers to a cumulative thickness of 14 mm, with the upper and lower surfaces exposed to the outside kept free of titanium film. The whole was wrapped with graphite paper and transferred to a graphite mold, and local reaction sintering and overall hot pressing sintering were carried out in sequence. The pressure of the local reaction sintering was 20 MPa, the temperature was 1650°C, and the insulation time was 25 min; the pressure of the overall hot pressing sintering was 35 MPa, the temperature was 2050°C, and the insulation time was 90 min, so that the boron carbide powder was completely porcelainized and then taken out of the furnace after cooling.

[0068] Comparative Example 1

[0069] The same as in Example 1, except that the magnetron sputtering titanium film deposition and local reaction sintering steps are omitted, and the layered pressed plate-shaped boron carbide blanks are stacked to form a composite boron carbide blank, and the boron carbide thick blank is directly pressed and formed in one go.

[0070] First, a commercially available phenolic resin (model: PF9502, Jinan Shengquan Group Co., Ltd.) was dissolved in anhydrous ethanol to form a solution with a concentration of 1 wt%.

[0071] Then, commercially available boron carbide powder with a D90 of 3 μm and boron carbide powder with a D90 of 0.5 μm (supplier: Mudanjiang Diamond Boron Carbide Co., Ltd.) were weighed at a mass ratio of 5:1, preliminarily mixed evenly, put into a grinding jar, and then further added with a prepared "phenolic resin + anhydrous ethanol" mixed solution (after conversion, the mass ratio of phenolic resin: boron carbide powder: anhydrous ethanol was 5:100:500), mixed and dispersed in a ball mill for 30 minutes, spray granulated and dried at 50°C to form boron carbide granules.

[0072] Subsequently, an appropriate amount of 80-120 mesh boron carbide pellets was sieved and weighed, poured into the mold cavity, and subjected to 100 MPa pressure holding for 2 min and 150 MPa pressure holding for 1 min at room temperature to form a boron carbide blank with a thickness of about 13 mm to 14 mm, which was then dried at room temperature.

[0073] Finally, the boron carbide blank is completely covered with graphite paper and transferred to a graphite mold. The temperature is raised to 2050°C, the pressure is loaded to 35MPa, and the heat and pressure holding time is 90 minutes. The boron carbide powder is completely transformed into porcelain through hot pressing and sintering, and then taken out of the furnace after cooling.

[0074] Comparative Example 2

[0075] The same as Example 2, except that the steps of magnetron sputtering titanium film deposition and local reaction sintering are omitted.

[0076] First, commercially available polyvinyl alcohol (model: BM-1, China Petrochemical Group Chongqing Chuanwei Chemical Co., Ltd.) was dissolved in deionized water to form a solution with a concentration of 1 wt%.

[0077] Then, commercially available boron carbide powder with a D90 of 3 μm and boron carbide powder with a D90 of 0.5 μm (supplier: Mudanjiang Diamond Boron Carbide Co., Ltd.) were weighed at a mass ratio of 4:1 and preliminarily mixed evenly, put into a grinding tank, and then further added with a prepared polyvinyl alcohol aqueous solution (after conversion, the mass ratio of polyvinyl alcohol: boron carbide powder: deionized water was 5:100:500), mixed and dispersed in a ball mill for 30 minutes, spray granulated and dried at 110°C to form boron carbide granules.

[0078] Subsequently, an appropriate amount of 80-120 mesh boron carbide granules was sieved and weighed, poured into the mold cavity, and subjected to 100 MPa pressure holding for 2 min and 150 MPa pressure holding for 1 min at room temperature to form a boron carbide thin plate blank with a thickness of 2 mm to 3 mm, which was then dried at room temperature.

[0079] Finally, the boron carbide thin plate blanks were stacked in multiple layers to a cumulative thickness of 14 mm, covered with graphite paper as a whole and transferred to a graphite mold. The temperature was raised to 2050°C, the pressure was loaded to 35 MPa, and the heat and pressure holding time was 90 minutes. The boron carbide powder was completely transformed into porcelain through hot pressing and sintering, and then taken out of the furnace after cooling.

[0080] The performance tests of the boron carbide ceramics obtained in Examples 1-3 and Comparative Examples 1-2 were performed respectively, and the results are shown in Table 1:

[0081] Table 1 Performance test results of embodiments and comparative examples

[0082]

[0083] As can be seen from Table 1, compared with the ordinary boron carbide ceramics in Comparative Examples 1 and 2, Example 1, Example 2, and Example 3 all use boron carbide ceramics with a toughness array, and their bending strength and fracture toughness are significantly improved; however, when the boron carbide ceramics in Example 3 are demoulded after being taken out of the furnace, it is found that the boron carbide ceramics are more adhered to the graphite paper and are locally deformed. It is speculated that the thicker titanium film causes the heat release to be more concentrated during sintering, the abnormal growth of boron carbide grains at the interface, and the higher internal stress in the ceramic after cooling. Therefore, in actual preparation, the titanium film on the surface of the boron carbide blank should not be too thick. Using a thin and uniform titanium film is more beneficial to the product performance and sintering quality of the boron carbide ceramic. The bending strength and fracture toughness of Comparative Examples 1 and 2 are not much different, which is speculated to be caused by errors in the sample preparation and testing process.

[0084] The present invention has been described in detail above. For those skilled in the art, without departing from the purpose and scope of the present invention, can implement the present invention in a wider range under equivalent parameters, concentrations and conditions. Although the present invention provides specific embodiments, it should be understood that the present invention can be further improved. In a word, according to the principle of the present invention, the application is intended to include any changes, uses or improvements to the present invention, including departing from the disclosed scope in the application and the changes made with conventional techniques known in the art.

Claims

1. A method for preparing boron carbide ceramics, characterized in that: The steps include: S1, depositing a pure titanium film on one side of a compression-molded plate-shaped boron carbide blank to obtain a titanium-clad boron carbide blank; S2. Stacking a plurality of the titanium-coated boron carbide blanks in an orderly manner along the thickness direction to obtain a composite boron carbide blank with multiple layers of titanium films spaced apart; wherein the titanium film surface and the titanium-free film surface of two adjacent titanium-coated boron carbide blanks are bonded; S3, sintering the composite boron carbide blank with the multi-layer titanium film spaced apart, and simultaneously generating a toughness layer by in-situ reaction between two adjacent boron carbide blanks to obtain the boron carbide ceramic.

2. The method for preparing the boron carbide ceramic according to claim 1, characterized in that: In step S1, the thickness of the titanium film is 0.10 μm to 5.00 μm, preferably 0.10 μm to 1.00 μm.

3. The method for preparing the boron carbide ceramic according to claim 1 or 2, characterized in that: In step S1, the thickness of the plate-shaped boron carbide blank is 2 mm to 5 mm.

4. The method for preparing a boron carbide ceramic according to any one of claims 1 to 3, characterized in that: In step S1, the deposition process of the titanium film includes any one of magnetron sputtering, physical vapor deposition, chemical vapor deposition, vacuum evaporation, ion implantation, plasma spraying, and chemical plating.

5. The method for preparing the boron carbide ceramic according to claim 4, characterized in that: The magnetron sputtering conditions are as follows: the magnetron sputtering is DC magnetron sputtering, and the operation is as follows: vacuum is evacuated to 1.5×10 -4 Pa, fill with 99.99% pure argon to 0.5Pa and maintain the argon flow rate at 30ml / min~50ml / min, maintain the sputtering power at 250W and the cathode negative bias at 80V, use a 99.9% pure titanium target, and deposit for 2min~60min.

6. The method for preparing a boron carbide ceramic according to any one of claims 1 to 5, characterized in that: In step S1, the method for preparing the plate-shaped boron carbide blank comprises the following steps: S11, mixing boron carbide powder, a binder and a solvent by ball milling, spray granulating and drying in sequence to obtain boron carbide granules; S12, pouring the boron carbide granules into a mold cavity for compression molding to obtain the plate-shaped boron carbide blank.

7. The method for preparing boron carbide ceramics according to claim 6, characterized in that: The boron carbide powder comprises boron carbide powder with a D90 of 1 μm to 4 μm and boron carbide powder with a D90 of 0.05 μm to 0.80 μm in a mass ratio of (3 to 7): 1; The binder is phenolic resin or polyvinyl alcohol; The mass of the binder is 1% to 8% of the boron carbide powder; The solvent is ethanol or water; The mass ratio of the boron carbide powder to the solvent is 1:(3-7); The ball milling time is 20min to 40min; The drying temperature is 40°C to 110°C; The mesh number of the boron carbide pellets is 80 mesh to 120 mesh; The compression molding process includes a first compression and a second compression. The first compression is to maintain the pressure at room temperature and 100 MPa for 2 minutes; the second compression is to maintain the pressure at room temperature and 150 MPa for 1 minute.

8. The method for preparing a boron carbide ceramic according to any one of claims 1 to 7, characterized in that: In step S2, the upper and lower outer surfaces of the composite boron carbide blank are free of titanium film; In step S2, the total thickness of the composite boron carbide blank with the multi-layer titanium film spaced apart is 8 mm to 15 mm; In step S3, the sintering includes local reaction sintering and overall hot pressing sintering performed successively; the pressure of the local reaction sintering is 15MPa~30MPa, the temperature is 1600℃~1700℃, and the insulation and pressure holding time is 10min~30min; the pressure of the overall hot pressing sintering is 30MPa~40MPa, the temperature is 2000℃~2300℃, and the insulation and pressure holding time is 60min~120min.

9. The boron carbide ceramic prepared by the method for preparing the boron carbide ceramic according to any one of claims 1 to 8.

10. Use of the boron carbide ceramics according to claim 9 in individual soldier plates or bulletproof armor.

Citation Information

Patent Citations

  • A preparation method and product of silicon carbide whisker toughened boron carbide ceramic composite material

    CN103833403B

  • Method for preparing graphene reinforcing boron carbide ceramic material

    CN108530082A

  • A multi-walled carbon nanotube-reinforced boron carbide-based ceramic material, its preparation method and application

    CN113004052B

  • A boron carbide ceramic, its preparation method and application

    CN113896552B

  • Preparation method of 3D structure reinforced boron carbide bulletproof flashboard

    CN115741976A